Technology Choice and Incentives under Relative Performance Schemes - Anja Schöttner; Matthias Kräkel (Verein für Socialpolitik, 2010)
We identify a new problem that may arise when heterogeneous workers are motivated by relative performance schemes: If workers' abilities and the production technology are complements, the firm may prefer not to adopt a more advanced technology even though this technology would costlessly increase each worker's productivity. Due to the complementarity between ability and technology, under technology adoption the productivity of a more able worker increases more strongly than the productivity of a less able colleague, thereby reducing the motivation of both workers to exert effort under a relative incentive scheme. We show that this adverse incentive effect is dominant and, consequently, keeps the firm from introducing a better production technology if talent uncertainty is sufficiently high and/or monitoring of workers is sufficiently precise.
Keywords: M55; J33; D82; 330; complementarities; heterogeneous workers; production technology; tournament